PERAN FASILITAS DAN HARGA UNTUK MENDORONG MINAT BERKUNJUNG DALAM SITUASI COVID 19 (STUDI PADA TAMAN HEWAN KOTA PEMATANGSIANTAR) - Sinaga, Onita Sari; Candra, Vivi; Putri, Debi Eka (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
Pematangsiantar Animal Park is one of the destinations often visited by locals and people from the outside of Pematangsiantar City. After several months of not operating, Pematangsiantar Animal Park made attempts to attract the community to interest in visiting the park during the new normal period. The objective of this study was to determine the effect of the facility and price on the interest in visiting the Pematangsiantar Animal Park. The research sample used in this study were active students of STIE Sultan Agung in even semester of the 2019/2020 academic year using a cluster sampling technique. The results of the study found that the correlation analysis of the facility, price, and interest in visiting had a very significant and positive relationship. The results of the coefficient of determination obtained R Square value of 0.666. The facility had a positive and significant effect on interest in visiting. The price had a positive and significant effect on interest in visiting.